PENYULUHAN DAN SKRINING GANGGUAN CEMAS DAN DEPRESI PADA TENAGA KESEHATAN DI LAYANAN PRIMER DI MASA PANDEMI COVID 19 - Panggabean, J.I.S.; Ariani, N.K.P; Kurniawan, L.S.; Wardani, I.A.K.; Ardani, I.G.A.I. (Buletin Udayana Mengabdi, 2023)
The spread of Covid-19 during the pandemic caused sudden and drastic social changes to the world community in various aspects. The Covid-19 pandemic period has been running for almost 2 years, with various adjustments at various levels of health facilities. However, health workers are still vulnerable to psychological pressure. This can lead to anxiety and depression disorders due to the pandemic situation and increased workload. This community service aims to provide counseling related to anxiety and depression disorders as well as to screen for anxiety and depression disorders in health workers in service during the COVID-19 pandemic at the Abiansemal I Health Center. This counseling attended by health workers at the Abiansemal I Health Center consisting of general practitioners, nurses, midwives, and other health workers. Anxiety and depression screening was performed using the Beck Depression Inventory, and Beck Anxiety Depression instruments. By conducting counseling, the health workers will gain additional knowledge about anxiety and depression disorders and be able to recognize symptoms of anxiety and depression. Screening is carried out to determine the level of anxiety and depression in health workers at the Abiansemal I Health Center so that appropriate treatment or intervention can be done. Keywords: Covid-19, Anxiety, Depression, Health worker, Primary service.